Negative Appraisals of the COVID-19 Social Impact Associated With the Improvement of Depression and Anxiety in Patients After COVID-19 Recovery - Chen, Wentao; Ju, Yumeng; Liu, Bangshan; Huang, Mei; Yang, Aiping; Zhou, Yun; Wang, Mi; Liao, Mei; Shu, Kongliang; Liu, Jiyang; Zhang, Yan (Frontiers in Psychiatry, 2021)
Objective: Little is known about the factors affecting the recovery of mental health in COVID-19 patients. The purpose of this study is to look into the changes of psychological distress and to explore the role of negative appraisals in the improvement of psychological distress in COVID-19 patients after they recovered from the infection. Methods: We conducted a longitudinal survey on patients with COVID-19 infection in Changsha. The 9-item Patient Health scale, the 7-item Generalized Anxiety Disorder scale and a newly developed measure, the COVID-19 Impact Scale (CIS) were applied to assess patients' depression, anxiety as well as negative appraisal towards COVID-19 infection during their hospitalization and one month after discharge. Results: Seventy-two patients were included in the analysis. A significant decrease in anxiety and depression levels was observed after patients discharged from hospital. Two meaningful factors of the CIS were extracted based on factor analysis, namely 'health impact', and 'social impact'. The change of social impact explained 12.7% and 10.5% variance in the depression and anxiety symptom improvement, respectively. Conclusions: Changes in negative appraisals, especially the appraisals related to COVID-19 social impact may play a vital role in relief of psychological distress of the infected patients. Therefore, a cognitive and social care perspective might be considered when promoting the mental health recovery and readjustment to society among COVID-19 patients.